PERANCANGAN SISTEM INFORMASI PERUMAHAN BERBASIS WEB PADA PT.CIPTA JAYA INHIL - A. Rafin (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2013)
Housing is a basic human need and need to be nurtured and developed for the survival and improve the lives and livelihoods of communities and settlements can not be seen as a means of sheer necessity , but more than that a man living in the process of creating living space to promote themselves and reveal his true identity. However , not all people can not easily build a house , takes a variety of things so that the house can be erected and occupied . Such as land ownership , structure , feasibility tests and trials , licensing of new building . Many people who do not want to be bothered with things like that , because it's the people who want to build or buy a house to take a more effective way and does not take up much time , that is by an agent to buy a house or a residential house which is called by the developer and payment can be made by cash or credit . With the increasing number of housing that sprung up in the city Tembilahan at this time , the public option will create a comfortable home tingal increasingly diverse and livable as well . A wide range of promotional programs offered to prospective customers ( home buyers ) with a variety of amenities and facilities owned completeness of each - each housing complex . However, not all potential customers can come to the location they are interested in housing , perhaps because they were busy or time constraint.Keyword: Housing, Depolover, Sales.